AN INVESTIGATION INTO SYNTACTIC, SEMANTIC FEATURES AND STYLISTIC MEANS OF EUPHEMISMS IN STORY OF KIỀU AND THEIR EQUIVALENTS IN ENGLISH VERSIONS - PHẠM THỊ NGỌC MẾN (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Euphemisms are famous for the glorification of the commonplace and for the elevation of the trivial. In the literary style, euphemisms are a means of beautifying the language in use and expressing the aesthetic value of the style. This study investigates euphemisms as a stylistic device in the story of Kiều and their equivalents in the English versions the terms of syntax, semantics and stylistics in these euphemisms. This qualitative study is carried out in a contrastive analysis with English as TL and Vietnamese as SL. Via this analysis, the study aims at presenting euphemisms employed in the masterpiece of Nguyễn Du. Also, the differences and the similarities between these euphemisms and their English equivalents are considered. In addition, we put forward some other translations for non-equivalents in English as well. Finally, the implications in teaching, learning, and translating euphemisms in both languages are dealt with.